Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x(2x-7)-4x+14=0
=>x(2x-7)-2(2x-7)=0
=>(x-2)(2x-7)=0
=>x-2=0 hoặc 2x-7=0
=>x=2 hoặc x=7/2
b, x(x-1)+2x-2=0
=>x(x-1)+2(x-1)=0
=>(x+2)(x-1)=0
=>x+2=0 hoặc x-1=0
=>x=-2 hoặc x=1
c, 2x^3+3x^2+2x+3=0
=>x2(2x+3)+2x+3=0
=>(x2+1)(2x+3)=0
=>x2+1=0 hoặc 2x+3=0
Vì x2+1>0 với mọi x ->vô nghiệm
=>2x+3=0 =>x=-3/2
d, x^3+6x^2+11x+6=0
=>x3+3x3+2x+3x2+3x3+6=0
=>x(x2+3x+2)+3(x2+3x+2)=0
=>(x2+3x+2)(x+3)=0
=>[x2+x+2x+2](x+3)=0
=>[x(x+1)+2(x+1)](x+3)=0
=>(x+1)(x+2)(x+3)=0
=>x+1=0 hoặc x+2=0 hoặc x+3=0
=>x=-1 hoặc x=-2 hoặc x=-3
a) x(2x-7)-4x+14=0
=>x(2x-7)-2(2x-7)=0
=>(x-2)(2x-7)=0
=>x-2=0 hoặc 2x-7=0
=>x=2 hoặc x=7/2
b, x(x-1)+2x-2=0
=>x(x-1)+2(x-1)=0
=>(x+2)(x-1)=0
=>x+2=0 hoặc x-1=0
=>x=-2 hoặc x=1
c, 2x^3+3x^2+2x+3=0
=>x2(2x+3)+2x+3=0
=>(x2+1)(2x+3)=0
=>x2+1=0 hoặc 2x+3=0
Vì x2+1>0 với mọi x ->vô nghiệm
=>2x+3=0 =>x=-3/2
d, x^3+6x^2+11x+6=0
=>x3+3x3+2x+3x2+3x3+6=0
=>x(x2+3x+2)+3(x2+3x+2)=0
=>(x2+3x+2)(x+3)=0
=>[x2+x+2x+2](x+3)=0
=>[x(x+1)+2(x+1)](x+3)=0
=>(x+1)(x+2)(x+3)=0
=>x+1=0 hoặc x+2=0 hoặc x+3=0
=>x=-1 hoặc x=-2 hoặc x=-3
x^2 -2x = 24
=> x^2 - 2x - 24=0
=>x^2 -8x+6x - 24 = 0
=> ( x^2- 8x)+( 6x-24) = 0
=> x(x-8) + 6(x-8) = 0
=> (x+6)(x-8)=0
=>\(\orbr{\begin{cases}x=-6\\x=8\end{cases}}\)
a) x2 - 2x - 3 = 0
x.(x - 2) = 3
x.(x - 2) = 3 . (3 - 2)
x = 3
b)2x2 +5x-3=0
x(2x+5)-3=0
x(2x+5)=3
x(2x+5)=-3(2.-3+5)
suy ra x=-3
a. 3x(x-2)-x+2=0
3x(x-2)-(x-2)=0
(3x-1)(x-2)=0
=>\(\hept{\begin{cases}3x-1=0\\x-2=0\end{cases}}\)
=> \(\hept{\begin{cases}3x=1\\x=2\end{cases}}\)
=>\(\hept{\begin{cases}x=\frac{1}{3}\\x=2\end{cases}}\)
vậy x thuộc (1/3;2)
a) ( x - 3 )2 - 4 = 0
<=> ( x - 3 )2 = 4
<=> \(\orbr{\begin{cases}\left(x-3\right)^2=2^2\\\left(x-3\right)^2=\left(-2\right)\end{cases}}\)
<=> \(\orbr{\begin{cases}x-3=2\\x-3=-2\end{cases}}\)
<=> \(\orbr{\begin{cases}x=5\\x=1\end{cases}}\)
Vậy S = { 5 ; 1 }
b) x2 - 9 = 0
<=> x2 = 9
<=> \(\orbr{\begin{cases}x^2=3^2\\x^2=\left(-3\right)^2\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
Vậy S = { 3 ; -3 }
c) x( x - 2x ) - x2 - 8 = 0
<=> x2 - 2x2 - x2 - 8 = 0
<=> -2x2 - 8 = 0
<=> -2x2 = 8
<=> x2 = -4 ( vô lí )
<=> x = \(\varnothing\)
Vậy S = { \(\varnothing\)}
d) 2x( x - 1 ) - 2x2 + x - 5 = 0
<=> 2x2 - 2x - 2x2 + x - 5 = 0
<=> -x - 5 = 0
<=> -x = 5
<=> x = -5
Vậy S = { -5 }
e) x( x - 3 ) - ( x + 1 )( x - 2 ) = 0
<=> x2 - 3x - ( x2 - x - 2 ) = 0
<=> x2 - 3x - x2 + x + 2 = 0
<=> - 2x + 2 = 0
<=> -2x = -2
<=> x = 1
Vậy S = { 1 }
f) x( 3x - 1 ) - 3x2 - 7x = 0
<=> 3x2 - x - 3x2 - 7x = 0
<=> -8x = 0
<=> x = 0
Vậy S = { 0 }
a) \(\left(2x+1\right)^2-4\left(x+2\right)^2=9\)
\(\left(2x+1\right)^2-\left[2\left(x+2\right)\right]^2=9\)
\(\left[2x+1-2\left(x+2\right)\right]\left[2x+1+2\left(x+2\right)\right]=9\)
\(\left(2x+1-2x-4\right)\left(2x+1+2x+4\right)=9\)
\(-3\left(4x+5\right)=9\)
\(4x+5=-3\)
\(4x=-8\)
\(x=-2\)
b) \(x^2-2x-15=0\)
\(x^2-5x+3x-15=0\)
\(x\left(x-5\right)+3\left(x-5\right)=0\)
\(\left(x-5\right)\left(x+3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-5=0\\x+3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=5\\x=-3\end{cases}}}\)
c) \(2x^2+3x-5=0\)
\(2x^2-2x+5x-5=0\)
\(2x\left(x-1\right)+5\left(x-1\right)=0\)
\(\left(x-1\right)\left(2x+5\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\2x+5=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\x=\frac{-5}{2}\end{cases}}}\)
\(x^2-2x=0\)
\(x.\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}\)
Vậy...
x=0
x=2